Study of the Floristic Diversity in Bissa Forest, Chlef, Algeria - Senouci, F.; Ababou, A.; chouieb, M.; Amrous, N.; Boukeffoussa Ghoul, N.H. (Algerian Journal of Research and Technology (AJRT), 2017)
The exceptional biological richness of Mediterranean ecosystems was highlighted by many researchers. As part of the Mediterranean basin, northern Algeria is characterized by a high plant biodiversity, estimated to almost 3139 species. In this context, this study focused on the floristic diversity in the Bissa forest, a cork oak forest in the Northwest of Algeria. Throughout the seven cantons of Bissa forest, 122 plant species belonging to 43 families were identified and listed in a local floristic database. The most dominant families in terms of species percentage were the Asteraceae and Fabaceae. The highest biodiversity was shown respectively by the cantons of Ain Lemcen, Oued Rihane and Tizerouine, while the lowest biodiversity was observed in the cantons of Yahia Bouzekri and Sidi M’hamed Aberkane. Through the phytosociological analysis, three major vegetation units with different numbers of diagnostic species with fidelity thresholds ranging from 0.17 to 1 were distinguished. Furthermore, many differential species with a wide ecological spectrum were observed. Finally five species have been identified as generalists present in all cantons and adapting to all conditions of this forest.